Aplicação de métodos de previsão de demanda em uma empresa de sucata localizada em Maracanaú/CE - Leite, Bárbara Cristina Carvalho (Universidade Federal Rural do Semi-Árido, 2020)
Organizations make predictions in their processes and the tabulation of the estimated data is to assist in the best decision making in relation to what may happen, and in response to these future moments, what will need to be accomplished. This work has the concept of applying demand forecasting methods in weighing trucks, in a company in the scrap business, located in the State of Ceará. This article aims to obtain data to examine and evaluate which type of truck appears most frequently in the service and consequently offers a greater financial return. For the production of this study, the quantitative research method was applied through the application of some demand forecasting methods, which were: Simple moving average with forecasting error, Exponential Smoothing Method and Simple Linear Regression. At the end of the application of the methods, the weekly demands were analyzed and the results served to guide and help the management of the enterprise in its business and planning.
Artigo
Keywords: Modelos de previsão; Pesagem de caminhão; Planejamento; Erros de previsão; Tomada de decisão; Forecasting models; Weighing truck; Planning; Forecasting errors; Decision making; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA